Characteristics of the Military Academy Cadet’s Language Register - Patmawati Ilyas Catur Pamungkas; Hari Wahyono (Universitas Indraprasta PGRI, 2022)
Language variations that appear in a conversation because of their use are called registers. Registers are used in a particular community to identify and characterize a job or group. The register language in this particular group is usually not found in other communities or other groups. The research method used is literature study or documentation related to the object of study under study. Several documents that contain or explain about the life of cadets are used as data sources. This article describes the Military Academy cadet register which has a characteristic that is its language is short, concise, and firm. The Military Academy cadet register is concise and firm, marked by the many acronyms and abbreviations used in addition to other vocabulary in the form of words and phrases. The vocabulary in the form of words, phrases, acronyms, and abbreviations is a vocabulary that is only found in the cadet community during the four years of military education in the Tidar Valley.Keywords: Characteristics, language variation, language register.